2015
DOI: 10.1371/journal.pone.0118135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ferulic Acid and γ-Oryzanol on High-Fat and High-Fructose Diet-Induced Metabolic Syndrome in Rats

Abstract: BackgroundThe high morbidity of metabolic dysfunction diseases has heightened interest in seeking natural and safe compounds to maintain optimal health. γ-Oryzanol (OZ), the ferulic acid (FA) ester with phytosterols, mainly present in rice bran has been shown to improve markers of metabolic syndrome. This study investigates the effects of FA and OZ on alleviating high-fat and high-fructose diet (HFFD)-induced metabolic syndrome parameters.MethodsMale SD rats were fed with a regular rodent diet, HFFD, or HFFD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
124
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 55 publications
14
124
0
5
Order By: Relevance
“…This polyphenolic compound has strong antioxidant activity which was confirmed in in vivo studies [27][28][29]. Li et al [30], who studied the ethanolic extract, have reported that leaves of common buckwheat contained 2.07/100 mg DW of ferulic acid.…”
Section: Discussionmentioning
confidence: 80%
“…This polyphenolic compound has strong antioxidant activity which was confirmed in in vivo studies [27][28][29]. Li et al [30], who studied the ethanolic extract, have reported that leaves of common buckwheat contained 2.07/100 mg DW of ferulic acid.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, only γ-oryzanol treatment is more effective than FA in significantly decreasing the liver index and hepatic triglyceride content. Decreased serum C-reactive protein and IL-6 levels and increased serum adiponectin concentration confirmed that FA and γ-oryzanol can be used as dietary supplements to alleviate the deleterious effects of HFFD [57]. Adenosine, in particular, effectively mitigates metabolic syndrome in SHRSP [50].…”
Section: Metabolic Disorder Aspectsmentioning
confidence: 75%
“…Interestingly, the antidiabetic and antidyslipidemic activities of rice bran have been reported in different animal model experiments [15][16][17]. Furthermore, the active components in processed rice bran promote health; indeed, the processing itself adds value to the rice bran [18,19]. Such treated rice bran may protect against metabolic syndrome by attenuating hypertension, dyslipidemia and insulin resistance; it is a candidate functional food because it prevents oxidative stress in rat and mouse models [20][21][22][23].…”
Section: Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, this study found that FA reduced the expression of hepatic lipogenic genes such as sterol regulatory element-binding protein 1c (SREBP1c), fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) along with upregulating hepatic carnitine palmitoyltransferase 1a (CPT1a) and peroxisome proliferator activated receptor alpha (PPARα) [32]. FA at a dose of 2.6 mmol/kg diet was effective at reducing inflammatory, hyperlipidemia, hyperglycemia markers in a highfructose, high-fat diet-induced model of metabolic syndrome [33]. A similar study found that FA minimized insulin resistance, vascular dysfunction and remodeling in a rat model of high-carbohydrate, highfat diet-induced metabolic changes, which may be realized through suppression of oxidative stress, down-regulation of p47phox, increased nitric oxide bioavailability with up-regulation of endothelial nitric oxide synthase and suppression of tumor necrosis factor-α (TNF-α) [34].…”
Section: Discussionmentioning
confidence: 99%